ENFORCEMENT OF LAWS ON SEXUAL VIOLENCE IN MARRIAGE (MARITAL RAPE): A COMPARATIVE STUDY OF CRIMINAL LAWS IN INDONESIA AND SINGAPORE - Wahdah, Azzhara Nikita; Harefa, Beniharmoni (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Marital rape is a form of sexual violence that is often not explicitly recognized in legal systems, especially in countries with strong patriarchal cultures. This article provides a comparative analysis of the regulation and enforcement of marital rape as a criminal offense in Indonesia and Singapore. In Indonesia, the recognition of marital rape as a criminal offense has been strengthened through the new Criminal Code (Law No. 1 of 2023), the PKDRT Law, and the TPKS Law, although its implementation still faces challenges in the form of complaint offenses, social stigma, and a lack of understanding of gender issues among officials. Meanwhile, Singapore has removed legal immunity for husbands since the enactment of the Criminal Law Reform Act 2019, and provides civil protection through Personal Protection Orders (PPOs) and an integrated reporting system. This study uses a normative legal and comparative law approach to examine the differences in the legal systems, regulations, and cultures of the two countries. The results of the study show that Singapore is more progressive in handling cases of marital rape, both in terms of regulations and victim protection mechanisms. This article recommends that Indonesia strengthen inter-agency synergy, reform the reporting system, and improve public legal literacy as strategic steps in combating domestic sexual violence. With a comprehensive approach, it is hoped that the Indonesian legal system can be more responsive to the needs of victims and ensure gender sensitive justice.